Impacts of Rural Development on Human Development in Indonesia - Hadiwibowo, Yuniarto; Setiya, Tanda; Raharjo, Taufik (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2025)
Research Originality: This study presents a new analysis of the determinants of human development to implement the government’s vision of building Indonesia from the village and grassroots.Research Objectives: This study aims to determine the effects of rural development and fiscal policy on human development in Indonesia.Research Methods: This study uses data from 434 municipalities for the 2017-2023 period. The study employs panel data analysis with the Common Effect Model, Fixed Effect Model, Random Effect Model, and Generalized Estimating Equation.Empirical Results: The findings suggest that rural development, economic development, and expenditures on goods & services contribute to human development. In contrast, the COVID-19 pandemic and capital expenditures affect human development negatively. The negative effects of capital expenditures become positive after they become assets.Implications: The finding implies the important role of rural development in fostering human development. Short-run objectives might be achieved by goods & services expenditures. Capital expenditures should be directed toward long-run objectives. The central government may accelerate human development by transferring assets to the local government.JEL Classification: E62, H75, I38, O15How to Cite:Hadiwibowo, Y., Setiya, T., & Raharjo, T. (2025). Impacts of Rural Development on Human Development in Indonesia. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 53-64. https://doi.org/10.15408/sjie.v14i1.44453.